A new brachypterous species of Phoberus MacLeay (Coleoptera: Trogidae) and status changes of species in the East African P. nigrociliatus group - Strümpher, Werner P.; Scholtz, Clarke H. (Zootaxa, 2017)
A new brachypterous species, Phoberus nyikanus Strümpher (Coleoptera: Trogidae), is described from Malawi. In addition, three status changes are proposed: Phoberus nigrociliatus (Kolbe) from the Ethiopian highlands, P. nyansanus (Haaf) from central East Africa, and P. nyassicus (Haaf) from southern Tanzanian mountains are elevated to species level. A key is provided to aid in the identification of members of the P. nigrociliatus group, and the species in the group are illustrated by photographs. This brings the total number of species in the genus to 44.